2022
DOI: 10.12741/ebrasilis.v15.e977
|View full text |Cite
|
Sign up to set email alerts
|

The Brazilian Legal Amazon Odonatofauna: a perspective of diversity and knowledge gaps

Abstract: The Brazilian legal Amazon occupies approximately 61% of its territory, covering a large part of Brazil's biodiversity. This large territorial dimension generates huge gaps in the animal diversity understanding, for example, the poor knowledge regarding the Odonata order. Worldwide, Odonata has almost 6,500 described species, with approximately 1,800 being recorded for the Neotropical region. Data on the Odonata order in the legal Amazon is still scarce, mainly due to its particularities, and little is known a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In total, 140 species were recorded for the Acre state, becoming the fifth second the greatest diversity of Odonata in the Northern region, only behind Amazonas (n = 364), Pará (n = 310), Mato Grosso (n = 285) and Rondonia (n = 206) (García-Júnior et al 2022). Following, we have the states of Amapá with 119 (Garcia Junior et al 2022) and Roraima with 82 species (Garcia-Junior et al 2022). However, considering that the information gathered in our study represents only a portion of the Acre state, we cannot rule out the possibility that this number could be even higher.…”
Section: Discussionmentioning
confidence: 96%
“…In total, 140 species were recorded for the Acre state, becoming the fifth second the greatest diversity of Odonata in the Northern region, only behind Amazonas (n = 364), Pará (n = 310), Mato Grosso (n = 285) and Rondonia (n = 206) (García-Júnior et al 2022). Following, we have the states of Amapá with 119 (Garcia Junior et al 2022) and Roraima with 82 species (Garcia-Junior et al 2022). However, considering that the information gathered in our study represents only a portion of the Acre state, we cannot rule out the possibility that this number could be even higher.…”
Section: Discussionmentioning
confidence: 96%
“…However, the distribution of most species is restricted, and species composition varies significantly between sites, indicating high beta diversity. In the last eight years, there has been an increase by 102 species recorded from the state of Amazonas (Garcia Júnior et al, 2022). This number rose from 262 recorded species in 2014 to 364 in 2022, an increase of 38.93% (Garcia Júnior et al, 2022;.…”
Section: Introductionmentioning
confidence: 99%
“…In the last eight years, there has been an increase by 102 species recorded from the state of Amazonas (Garcia Júnior et al, 2022). This number rose from 262 recorded species in 2014 to 364 in 2022, an increase of 38.93% (Garcia Júnior et al, 2022;. However, as with the rest of the country, collection efforts are not evenly distributed across the state.…”
Section: Introductionmentioning
confidence: 99%
“…A brief literature review revealed that Odonata inventory studies have been published in the following states: Ceará (Takiya et al 2016), Sergipe (Santos et al 2020), Bahia (Ribeiro et al 2021a), Paraíba (Koroiva et al 2021), and Alagoas (Godé & Ferreira-Peruquetti 2015, Farias et al 2023). In addition, there are studies on occurrence records of species in other northeastern states (Mesquita & Matteo 1991, De Marco-Júnior 2008, Carvalho & Bravo 2014, Irusta & Lencioni 2015, Nobre 2016, Bastos et al 2019, Lacerda & Machado 2019, Ribeiro et al 2021b, Garcia-Junior et al 2022, Koroiva et al 2022.…”
Section: Introductionmentioning
confidence: 99%